Selective separation of amines from continuous processes using automated pH controlled extraction. Issue 10 (31st August 2021) - Power, Luke A.; Clayton, Adam D.; Reynolds, William R.; Hose, David R. J.; Ainsworth, Caroline; Chamberlain, Thomas W.; Nguyen, Bao N.; Bourne, Richard A.; Kapur, Nikil; Blacker, A. John
Abstract : An automated separation system is described for identifying the optimal conditions for purifying an amine from a mixture. Abstract : We present a rapid continuous processing methodology to screen for the optimal, selective, liquid–liquid extraction conditions, from a typical post-reaction mixture of amines, using both inline and online analysis to systematically alter the pH, by controlling the acid addition pump. A mixture of 95% α-methyl-benzylamine, 1, and 5% N -benzyl-α-methyl-benzylamine, 2, simulated a reaction product and impurity, with the former extracted from toluene into water with 92% efficiency and 99% purity. The initial acid concentration and outlet pH (post-extraction), were compared with the amine concentration in each phase. The incorporation of inline, pH and HPLC, monitoring of both the aqueous and organic phases, allowed for detailed analysis of the applied extraction conditions. This produced an autonomous system for exploring the amine extraction conditions: optimal amount of acid and organic-aqueous phase ratio.